1997
DOI: 10.1088/0957-0233/8/7/020
|View full text |Cite
|
Sign up to set email alerts
|

A combined unit for viscosity, surface tension and density measurements in oxide melts

Abstract: A combined experimental unit for high-temperature viscosity, density and surface-tension measurements in oxide melts (glasses, metallurgical slags and coal ash) is described. The high-temperature viscometer is based on the Brookfield device whereas the density and surface-tension measurements are based on the maximum-bubble-pressure method. A vertical tube furnace is capable of reaching temperatures up to 1550 • C. An inert (argon) atmosphere allows the use of non-standard, molybdenum spindles for viscosity me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…Consequently, fast measurement of these three parameters is strongly recommended. Roach reported a new method to dynamically measure surface tension, density and viscosity of melts [11], and Vaisburd described a combined unit for measuring surface tension, density, and viscosity of oxide melts [12]. However, in Roach method, surface tension, density and viscosity were measured according to a modified Bernoulli formulation, and Vaisburd used the maximum bubble pressure method, which period is longer than 2 min, to measure these three parameters of oxide melts, therefore, they are not adequate for fast measurement and thus there is a need to develop a new device.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, fast measurement of these three parameters is strongly recommended. Roach reported a new method to dynamically measure surface tension, density and viscosity of melts [11], and Vaisburd described a combined unit for measuring surface tension, density, and viscosity of oxide melts [12]. However, in Roach method, surface tension, density and viscosity were measured according to a modified Bernoulli formulation, and Vaisburd used the maximum bubble pressure method, which period is longer than 2 min, to measure these three parameters of oxide melts, therefore, they are not adequate for fast measurement and thus there is a need to develop a new device.…”
Section: Introductionmentioning
confidence: 99%
“…[1] the liquid-slag sample did not change the slag composition Calibration of the high-temperature viscometer was based with regard to the oxide components, but it had an affect initially on measurements made on a borax melt, while later on the nonferrous metal concentration in slag. The chemical calibrations were made using a ternary eutectic in the system analysis showed that the copper content in the slag samples CaO-Al 2 O 3 -SiO 2 (point 5, the anorthite glass eutectic).…”
mentioning
confidence: 99%
“…EXPERIMENTAL RESULTS knife edge. [1] Measurements were made in the temperature range from 1350 ЊC to 1550 ЊC for the slag and in the The results are presented in Tables II through IV and range from 1350 ЊC to 1500 ЊC for the matte. The estimated Figures 2 and 3.…”
mentioning
confidence: 99%
“…Considering that infiltrations were studied up through 10 h, utilizing static values that were achieved over the course of minutes should be acceptable. A surface tension of 0.5 N/m and a contact angle between the slag and the refractory of roughly 20 ° at 1400 ° C were considered. Finally, as the pore radius at the fluid head governs the ultimate penetration depth, the average pore radius, acquired from the mercury porosimetry measurements, of 0.92 μm was used.…”
Section: Discussionmentioning
confidence: 99%